Assessing the effects of antidepressant use on stroke recurrence and related outcomes in ischemic stroke patients: a propensity score matched analysis - Alamri, Faisal F.; Almarghalani, Daniyah A.; Alatawi, Yasser; Alraddadi, Eman A.; Babateen, Omar; Alayyafi, Ahmed; Almalki, Ziyad; Alsalhi, Khaled; Alzahrani, Khaled; Alghamdi, Ahmed; Aldera, Hussain; Karamyan, Vardan T. (Frontiers in Pharmacology, 2025)
The effect of antidepressant use, particularly that of selective serotonin reuptake inhibitors, on stroke outcomes remains unclear. This hospital-based, retrospective, observational study utilized propensity score-matching (PSM) to assess the association between antidepressant use, stroke-related outcomes, and complications. The study was conducted at King Abdulaziz Medical City (KAMC) in Jeddah and Riyadh and included 1,125 patients with acute-subacute ischemic stroke, of whom 1,025 were antidepressant non-users and 100 antidepressant users. After PSM, 200 patients (100 antidepressant users and 100 non-users) were included in the final analysis. This study aimed to assess the association between antidepressant use, stroke recurrence, and mortality. Additionally, the study examined the association between antidepressant use and stroke severity, functional independence, and incidence of post-stroke complications. The Kaplan-Meier analysis revealed no statistically significant differences in stroke recurrence (p = 0.5619) or mortality (p = 0.6433) between antidepressant users and non-users over the 1-year follow-up period. Additionally, no significant differences were observed in stroke severity at admission and discharge (p = 0.33210 and p = 0.78410, respectively) or functional independence (p = 0.9176 and p = 0.4383, respectively) between the two groups. These findings suggest that antidepressant use does not significantly affect stroke recurrence, mortality, stroke severity, or functional independence. However, further large-scale studies are warranted to validate these findings and investigate potential confounding factors, such as stroke subtypes, co-use of certain medications, and physical activity.